Analisis Resepsi Anggota Komunitas Visual Whisperer Project Mengenai Pembohongan Publik dalam Program Q&A di Metro Tv - Josafat Ririmasse; Dyah Kusumawati (UNIVERSITAS KALBIS, 2022)
Belaga Hollywood is someone who considers himself already in the Hollywood realm but actually has not yet reached that stage. The researcher gave the title of this research to see how the Visual Whisperer Project members interpret the information on the Belaga Hollywood episode Q&A program by using three position categories, namely the position of dominant hegemony, negotiation, and opposition. This study uses a qualitative approach to the type of descriptive research and encoding-decoding theory by Stuart Hall. Researchers analyzed using audience reception analysis methods. The results showed there were differences in meaning in each of the information described in the Belaga Hollywood Q&A program. The position of the audience is dominated by the dominant hegemony position in Hollywood Belaga Title information, the Meaning of Incontention, Media Release which contains Livi Zheng films competing with Avengers, Utilizing public ignorance, and Criticism for National Media. The meaning of the opposition is in the directors' information. The negotiating position becomes a meaning that does not dominate any information on the Belaga Hollywood Q&A program.